Sport and people with disabilities: what is the contribution of Sport Psychology studies? - Alves, Mateus Egilson da Silva (2022)
Sport Psychology is still a recent area of Psychology, however, has been gaining rapid theoretical-practical growth in recent years, being increasingly valued, whether when analyzing the dimension of psychological aspects in the performance of athletes, or in how sport acts as a positive factor in the individuals' lives. However, it’s noted that little approaches in the literature that intersect the psychology of sport aimed at people with disabilities - PWD, or even in Adapted Sport. The objective of this study was to produce a theoretical essay about sport psychology among people with disabilities. It is a qualitative, exploratory and descriptive study, carried out through a narrative review, seeking to investigate the information available on certain topics, but without the rigor of a systematic review. Two main premises can be learned from the current literature, the first that is dedicated to reporting the interactions between sport psychology and people with disabilities, as well as the current scenarios of these issues, and the second that delves into the aspects of the sports psychology and people with disabilities in the broader field of Psychology. It can be concluded that sport psychology is already consolidated as a fertile area of psychology, however, the literature in this field for people with disabilities is limited, and more studies are needed on the intersections of adapted sport in sport psychology.